CSR for purpose, shared value and deep transformation : the new responsibility - Munro, Virginia (Emerald Publishing Limited, 2020)
CSR for Purpose, Shared Value and Deep Transformation focuses on a new type of CSR, which includes entrepreneurial innovation, sustainable goals and shared and integrated value in a systems-oriented approach for deep transformation. All topics are backed by case studies, academic literature and future research opportunities.